A systematic evaluation and comparison of the consistency of infant safer sleep messaging in Australia - Kruse, Sarah P.; D’Souza, Levita; Young, Jeanine; Tuncer, Hannah G. G. (Frontiers in Communication, 2025)
To reduce the occurrence of sudden infant death, organisations have created recommendations about infant safer sleep and shared sleep. With the considerable volume of documents, consistency in messaging is paramount to reduce caregiver confusion and to reduce engagement in practices deemed to be unsafe for their infant. This review aimed to systematically compare documents that contain recommendations on infant safer sleep, including shared sleep, in Australia. Documents were identified by researchers with subject matter expertise, and through a systematic webpage search. A total of n = 32 eligible documents were included from n = 26 organisations. If an organisation had a separate document for shared sleeping, both documents were included and reviewed together. Consistency of recommendations were evaluated against the recommendations within the International Society for the Study and Prevention of Perinatal and Infant Death’s (ISPID)‘s guidelines, while the approach taken to discuss shared sleep from via Risk Minimisation vs. Risk Elimination was also evaluated using a coding framework. No organisation’s document/s contradicted ISPID’s guidelines, although there was variation in the quantity included. The approaches taken towards shared sleep by organisations were diverse between Risk Elimination and Risk Minimisation. Strategies to engage in safer shared sleep were provided by less than half of the organisations, as was the acknowledgement of familial, cultural, or logistical preferences for shared sleep, or that shared sleep may also occur unintentionally. Most organisations recommended that infants be breastfed but did not discuss the bi-directional link between breastfeeding and shared sleeping. Organisations need to provide consistent messaging on infant safer sleep to avoid public confusion. The adoption of a Risk Minimisation approach with clearer messaging provides considerations for informed choice, and strategies for safer shared sleeping; intentional or unintentional.